L’utilisation des nouvelles technologies au service de l’histoire des femmes et du genre. À propos du projet de base de données Eurykleia - Nathalie Ernoult; Letticia Leite; Camille Noûs (Genre & Histoire)
The Eurykléia project proposes to develop an online-database by collecting documents that mention women by their own names who lived in Greek and Roman Antiquity (8th century BCE – 5th century CE). Each name thus collected is restored in the context of its production (epic, dramatic, philosophical, historical, poetic, legal texts, honorary inscriptions, inscriptions on coins, vases, graffiti etc.) and in its mode of enunciation (laudatory discourse, discourse of blame, gender-neutral discourse). This database offers the scientific community an overall view of women’s private and public lives in Greek and Roman cities, and provides a strong statistical tool for women and gender studies, devoid of historiographical a priori.